The Influence of Price and Service Quality on Consumer Satisfaction at Seblak Gaul Ciater Barat Resto - Rahayu, Suharni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research analyzes the impact of price and service quality on consumer satisfaction at Resto Seblak Gaul in West Ciater using a descriptive quantitative method with a sample of 100 respondents. Data analysis included validity, reliability, regression, and hypothesis testing. Results show that price (t-value: 7.474 > t-table: 1.984) and service quality (t-value: 18.225 > t-table) both have a positive and significant effect on consumer satisfaction. Together, price and service quality also significantly influence satisfaction (F-value: 170.602 > F-table: 3.090), as indicated by the regression equation Y = -306 + 0.100X1 + 0.531X2. The study's demographic consists of 82,656 consumers who have made purchases at Resto Seblak Gaul Ciater Barat. The sample size was calculated using the Slovin algorithm with a 10% margin of error, yielding 100 responses.